A rotatividade de professores na Educação Infantil: e as crianças como ficam? - Lucca, Priscilla Giatti de (2018)
This study aimed to investigate ways of minimising the effects generated by the teachers’ turnover in the Children Education, regarding the establishment of emotional bonds – safe – with the babies and children, without creating a sudden break which would compromise their development. The period of the research was from 2013 to 2017 years in a Children Education Centre (CEC) which serves children with 0 to 3 years and 11 months age, situated in the peripheral region of the South area of the city of São Paulo. In order to develop the research, a document analysis of the legislation regulating the teachers’ removal in the Municipal System of São Paulo and an inventory of the records from the teachers’ attendance book of this Scholar Unity in order to identify the teacher’s stay or not stay. Another methodological procedure was the critical incidents trigger which was organized for an initial discussion with the 11 teachers who were also part of the focal group, with the aim to discuss the effects generated by these professionals’ turnover in this CEC. The critical incidents sensitized the teachers regarding the presented problem and in relation to the search for actions toward the confrontation of the teacher mobility intending to minimize the baby and children’s sorrow and to provide a greater affective and emotional security for their whole development. From the performed analysis it was possible to realise that the Scholar Unity has a high index of turnover in the course of the academic year. The political organization to the hiring, the closure or the displacement of the teachers does not match the needs of the babies and children since it happens in an uncontrolled way and in several moments during the academic year. Furthermore, it was identified the need of clearing the look of the managers, teachers, and families in order to promote a new reflection about the theme. Therefore, this research proposes some actions regarding the care in the welcoming of the entrant teacher of which highlight the need to allow the new teacher adaptation in order to develop the safe attachment and affective bonds with the babies and children, providing a health environment in every respect for the Early Childhood